Fear of negative evaluation is associated with altered brain function in nonclinical subjects - Kajimura, Shogo; Kochiyama, Takanori; Nakai, Ryusuke; Abe, Nobuhito; Nomura, Michio (Psychiatry research. Neuroimaging, 2015)
Social anxiety disorder (SAD), which involves excessive anxiety and fear of negative evaluation, is accompanied by abnormalities in brain function. While social anxiety appears to be represented on a spectrum ranging from nonclinical behavior to clinical manifestation, neural alteration in nonclinical populations remains unclear. This study examined the relationship between psychological measures of social anxiety, mainly using the Fear of Negative Evaluation Scale (FNES), and brain function (functional connectivity, degree centrality, and regional betweenness centrality). Results showed that FNES scores and functional connectivity of the parahippocampal gyrus and orbitofrontal cortex and the betweenness centrality of the right parietal cortex were negatively correlated. These regions are altered in SAD patients, and each is associated with social cognition and emotional processing. The results supported the perspective that social anxiety occurs on a spectrum and indicated that the FNES is a useful means of detecting neural alterations that may relate to the social anxiety spectrum. In addition, the findings indicated that graph analysis was useful in investigating the neural underpinnings of SAD in addition to other psychiatric symptoms. •FNE was associated with weakened functional connectivity in memory-/affect-related regions.•FNE was associated with decreased betweenness centrality in the right parietal region.•Graph analysis is useful in investigating the neural underpinnings of social anxiety disorder.